Synthesis, Characterisation, and Functionalisation of Charged Two-Dimensional MoS2 - Mc Donald, Aidan (My University, 2023)
The applications of exfoliated MoS2 are limited by its inert surface and poor interface. We have activated the surface of exfoliated 2H-MoS2 by reacting it with NaBH4, forming an n-doped material as demonstrated by a negative zeta-potential value ζ=−25 mV and a 20 nm (0.05 eV) red-shift in its photoluminescence spectrum. The novel material's spectral properties were consistent with pristine 2H-MoS2 (as determined by HR-TEM, XPS, pXRD, DRIFT, TGA, and Raman spectroscopy). Importantly, it was readily dispersed in H2O unlike 2H-MoS2. Its dispersibility properties were explored for a variety of solvents and could be directly correlated with the relative permittivity of the respective solvents. The charged 2H-MoS2 reacted readily with an organo-iodide to deliver functionalized 2H-MoS2. Our approach delivers aqueous dispersions of semiconducting 2H-MoS2, without additives or chemical functionalities, and allows for controlled and facile functionalization of 2H-MoS2 opening multiple new avenues of semi-conducting MoS2 application.
PUBLISHED
Keywords: exfoliated MoS2; photoluminescence spectrum; Raman spectroscopy